Development of acute severe right heart failure after transcatheter aortic valve implantation in patient with left ventricle assist device-acquired aortic regurgitation - Zübeyde Bayram; Cem Doğan; Emre Gürcü; Cihangir Kaymaz; Nihal Özdemir (KARE Publishing, 2020)
A 58-year-old man with a left ventricular assist device (LVAD), which had been implanted 1 year earlier, presented with rest dyspnea. Moderate to severe aortic regurgitation (AR), pre-postcapillary pulmonary hypertension, modarete right ventricular (RV) failure, and low cardiac output were observed at presentation. Transcatheter aortic valve implantation (TAVI) was performed to treat the AR and a self-expandable aortic valve was implanted. Within minutes, hypotension, RV and inferior vena cava dilatation, and left atrial (LA) and left ventricular (LV) collapse occurred and persisted despite LVAD speed reduction. It was observed that severe RV failure had developed and venoarterial extracorporeal membrane oxygenation (VA-ECMO) was applied. Following VA-ECMO treatment, the RV dimensions decreased, and the LA and LV dimensions began to increase, as well as the LVAD flow. Weaning from VA-ECMO was unsuccessful and exitus occurred on the fifth day after TAVI secondary to RV failure. It was surmised that the decrease in blood circulation from the aorta to the LV after treatment of severe AR with TAVI caused an acute increase in the cardiac output and the RV preload. The acute increase in the RV preload led to acute severe right heart failure. It is necessary to prepare the RV to compete with an acute increase in preload before TAVI even when there is only modarete RV failure.